The 68-kDa Telomeric Repeat Binding Factor 1 (TRF1)-associated Protein (TAP68) Interacts with and Recruits TRF1 to the Spindle Pole during Mitosis - Lan, Jianping (American Society for Biochemistry and Molecular Biology, 2014)
The telomere capping protein TRF1 is a component of the multiprotein complex “shelterin,” which organizes the telomere into a high order structure. Besides telomere maintenance, telomere-associated proteins also have nontelomeric functions. For example, tankyrase 1 and TRF1 are required for the maintenance of faithful mitotic progression. However, the functional relevance of their centrosomal localization has not been established. Here, we report the identification of a TRF1-binding protein, TAP68, that interacts with TRF1 in mitotic cells. TAP68 contains two coiled-coil domains and a structural maintenance of chromosome motifs and co-localizes with TRF1 to telomeres during interphase. Immediately after nuclear envelope breakdown, TAP68 translocates toward the spindle poles followed by TRF1. Dissociation of TAP68 from the telomere is concurrent with the Nek2A-dependent phosphorylation at Thr-221. Biochemical characterization demonstrated that the first coiled-coil domain of TAP68 binds and recruits TRF1 to the centrosome. Inhibition of TAP68 expression by siRNA blocked the localization of TRF1 and tankyrase 1 to the centrosome. Furthermore, siRNA-mediated depletion of TAP68 perturbed faithful chromosome segregation and genomic stability. These findings suggest that TAP68 functions in mediating TRF1-tankyrase 1 localization to the centrosome and in mitotic regulation.